Peran Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Lumban Gaol, Nasib Tua; Siburian, Paningkat (Kelola: Jurnal Manajemen Pendidikan, 2018)
The purpose of this study was to explore how the principal should work at school. Six efforts can be implemented by school principal in enhancing the teacherâs performance including (1) to focus seriously on the improvement of teacher competencies, (2) to provide sufficient funding for improving teacher professionalism, (3) to supervise and guide teachers professionally, (4) to create a organizational culture of school that are comfortable for teachers, (5) to create innovation and advancement at school, and (6) to provide various rewards for each achievement that are done by teacher. Hence, it is recommended that school principal must more actively and creatively collaborate with teachers and educational stakeholder to conduct the improvement of teachersâ performance.